Vulnerability assessment of extended end-plate connections under mainshock-aftershock sequences - Benvenga, Risa Nicole, author; Mahmoud, Hussam, advisor; Chen, Suren, committee member; Senior, Bolivar, committee member (Colorado State University. Libraries, 2018)
After multiple seismic events in the mid 90s where welded connections performed poorly, bolted beam-to-column connections were investigated as a potential alternative. Extensive experimentation was performed to better understand the behavior of the joints, and models were developed in order to simulate their complex behaviors. The models included numerical finite element models, mathematical models, and mechanistic models. While all models have their limitations, mechanistic models have been shown to provide excellent balance between efficiency and accuracy in terms of analysis time and behavior prediction. In general, it has been shown than most models are able to accurately capture the behavior of the connections under monotonic and cyclic loading, representing the effect of mainshocks on connection behavior. However, research into the effects of mainshock-aftershock sequences that occur during many earthquakes on connection behavior has generally been lacking. Moreover, assessment of connection behavior, whether subjected to mainshock or mainshock-aftershock sequences, using a probabilistic framework has not received sufficient attention despite such analysis approaches being a basic requirement for performance-based engineering. This study included two overarching goals. The first goal was to utilize mechanistic models for assessment of behavior of end-plate connections under mainshock-aftershock sequences. The second goal was to employ the developed models in probabilistic analysis for the development of fragility functions that describe the probability of exceeding a specific limit state of the connection components for an increasing level of earthquake intensity. Specifically, for the first goal, two different strengths of extended end-plate connections were investigated. Component-based mechanical models in accordance with Eurocode 3 were developed to simulate the behavior of extended end-plate connections under mainshock-aftershock loading in this study. An understrength factor was developed in order to account for the inherent conservatism within Eurocode 3. For the second goal, fragility functions for the different failure modes and limit states, pertaining to the various connection components, were created based upon the results of a Monte Carlo simulation. The modulus of elasticity, yield strength, and ultimate strength were treated as random variables and the limits states evaluated included the bolts failing in tension, the column web failing in shear, and the exceedance of rotational limits. The analysis results show that the most likely mode of failure was that of the bolts in tension. It was also observed that the aftershock ground motions had a larger effect on probability of failure for strength limit states, while the mainshock had a larger effect on the probability of failure for the rotational limit states.
Keywords: earthquakes; mainshock-aftershock; end-plate connections; component-based modeling